JavaScript & jQuery - Duckett, Jon
Basic programming concepts - assuming no prior knowledge of programming beyond an ability to create a web page using HTML & CSS. Core elements of the JavaScript language - so you can learn how to write your own scripts from scratch. jQuery - which will allow you to simplify the process of writing scripts (this is introduced half-way through the book once you have a solid understanding of JavaScript). How to recreate techniques you will have seen on other web sites such as sliders, content filters, form validation, updating content using Ajax, and much more (these examples demonstrate writing your own scripts from scratch and how the theory you have learned is put into practice)